Integrasi Pendidikan Agama Kristen dengan Teknologi Digital dalam Membentuk Karakter Moral Generasi Z : Sebuah Kajian Pustaka - Gracia Natalia Nugroho; Wiwin Gita Bone; Yesika Mangasse Tandisau; Ira Oktavia; Febrianti Febrianti (Jurnal Pendidikan Dirgantara, 2025)
This study aims to comprehensively identify and map various models, strategies, and approaches to Christian Religious Education (CRE) learning that integrate digital technology with Christian values and their relevance to the formation of moral character in Generation Z, and to analyze Christian principles that need to be maintained along with innovative learning strategies to overcome the moral challenges of Generation Z in the digital era. This research uses a literature review method by analyzing 25 scientific journal articles published in 2023-2025 through thematic analysis techniques. The results show that there are five models of digital technology integration in CRE learning: platform-based digital learning, contextual-digital learning, collaborative-participatory learning, artificial intelligence-based learning, and hybrid learning. Implementation strategies include the use of interactive multimedia content, social media ministry, online learning communities, digital project-based learning, and immersive technology. Christian principles that need to be maintained include the supremacy of God's Word, learning centered on relationship with God, the importance of faith community, digital integrity, and balance between digital and direct spiritual experiences. This research provides theoretical contributions in the form of comprehensive mapping of technology integration in CRE and practical contributions in the form of recommended learning strategies that can be implemented to shape the moral character of Generation Z in the digital era.